PIXE analysis of Late La Tène scabbards with non-ferrous open-work plates (and associated swords) from Slovenia - Šmit, Žiga; Istenič, Janka; Perovšek, Sonja (Arheološki vestnik, 2010)
The method of proton-induced X-ray emission (PIXE) was applied for the analysis of late 1st century BC swords and associated scabbards with openwork copper-alloy plates from the Ljubljanica River, Strmec above Bela Cerkev, Ver-dun grave 37 and Verdun grave 131. The results indicate that iron and pure brass were used in the manufacture of these objects